2021
DOI: 10.48550/arxiv.2107.07991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Survival of Multiphase Dusty Clouds in Hot Winds

Ryan Jeffrey Farber,
Max Gronke

Abstract: Much progress has been made recently in the acceleration of ∼ 10 4 K clouds to explain absorption-line measurements of the circumgalactic medium and the atomic phase of galactic winds. However, the origin of the molecular phase in galactic winds has received relatively little theoretical attention. Studies of the survival of atomic clouds suggest efficient radiative cooling may enable the survival of expelled material from galactic disks. Alternatively, atomic and molecular gas may form within the outflow, if … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(196 reference statements)
0
5
0
Order By: Relevance
“…For example, this paper has presented consistent evidence of Si and Fe depletion in several sightlines through the OA and C, and this has potentially interesting implications. The survival of dust could provide insight regarding the physics of the HVCs, and insights on dust survival in high-velocity objects could help to explain molecular gas in galactic outflows (Farber & Gronke 2021). How ubiquitous is the dust?…”
Section: Discussionmentioning
confidence: 99%
“…For example, this paper has presented consistent evidence of Si and Fe depletion in several sightlines through the OA and C, and this has potentially interesting implications. The survival of dust could provide insight regarding the physics of the HVCs, and insights on dust survival in high-velocity objects could help to explain molecular gas in galactic outflows (Farber & Gronke 2021). How ubiquitous is the dust?…”
Section: Discussionmentioning
confidence: 99%
“…They may represent clouds that rapidly grew, were then differentially compressed in spiral arms and have later been shear-stretched in inter-arm regions (Shetty & Ostriker 2006). Alternatively, such clouds may represent inflow streams under the bar potential and/or outflows from the galactic disk (e/g., Kannan et al 2021;Farber & Gronke 2021). In any case, such dust lanes, partly traced by 12 CO emission, are likely interspersed with Hα-and diffuse X-ray-emitting plasma.…”
Section: Structure Of the X-ray Absorbing Gasmentioning
confidence: 94%
“…Therefore, the dusty gas should lie mainly away from the galactic plane and likely represent blown-out supershell walls interacting with a relatively slow rotating gaseous coronae of M83, probably similar to so-called intermediate velocity or even high-velocity dusty clouds or complexes (Marasco et al 2012). This interaction could lead to the observed lagging halo of cool gas (e.g., Peek et al 2009;Röhser et al 2016) and to the condensation of the coronal gas (Armillotta et al 2016;Vijayan et al 2020;Hobbs & Feldmann 2020;Dutta et al 2021;Gronke et al 2021). A systematic study of the interaction, confronted by the observed X-ray absorption properties, will thus help to understand the circulation of the cool dusty gas and plasma at galactic disk/halo interfaces (e.g., Armillotta et al 2016;van de Voort et al 2021).…”
Section: Structure Of the X-ray Absorbing Gasmentioning
confidence: 99%
“…In the self-shielding regime clouds will be able to cool to significantly lower temperatures (∼ 10 2 K) and higher densities, and in some cases the clouds own self-gravity will become significant (Girichidis et al 2021). This will have important observational implications as well as lead to modifications to the cloud-wind interaction (Farber & Gronke 2021). In principle it will be straightforward to modify our current cloud-wind interaction to include the ability for high column density clouds to cool to lower temperatures.…”
Section: Missing Ingredients and Model Extensionsmentioning
confidence: 99%